A retrospective analytical study of renal transplant patients over a period of two years - Rodrigo, P.C.; Sheriff, R.; Rajapakse, S.; Lanerolle, R.D.; Sheriff, M.H.R. (My University, 2009)
In view of increasing incidence of chronic renal failure in Sri Lanka and demand for transplantation, it is important to evaluate the outcome of current transplant programmes. Methods: This retrospective analytical study made a database of patients who underwent renal transplant under the Faculty of Medicine (Colombo) renal transplant programme during the two year period from 31st December 2004 to 31st December 2006. Statistical analysis was done using SPSS. Results / Discussions: There were a total of 73 (n=73) patients transplanted in the given time period, 46 (62.5 %) at National Hospital and 27 (37.5 %) at Western infirmary. Eighteen (29.1 %) had died by February 2007 of all patients traced. Forty three patients (58.3%) were interviewed and twelve patients could not be contacted. Of the interviewed, 28 (38.9%) were on azathioprin, prednisolone and cyclosporin while 15 (20.8%) were on prednisolone, cyclosporine and mycophenolate mofetil. In the sample, 4 patients had cytomegalovirus (CMV) and 5 had tuberculosis (TB) post transplant. Out of all infections, the most commonly reported one was urinary tract infection (11 cases). There was no significant benefit in protection against acute rejection in those who took induction therapy. There was no statistically significant difference in surgical complications or survival depending on center of transplant. Conclusion: The numbers were too small to calculate a statistically significant vulnerability to infections depending on immunosuppressant regimen. Those who received induction therapy did not have a significantly low rate of acute rejection than others.